Xylose consumption and ethanol production by Pichia guilliermondii and Candida oleophila in the presence of furans, phenolic compounds, and organic acids commonly produced during the pre-treatment of plant biomass - da Silva, Ronivaldo Rodrigues [UNESP]; Zaiter, Mohammed Anas [UNESP]; Boscolo, Maurício [UNESP]; da Silva, Roberto [UNESP]; Gomes, Eleni [UNESP] (Springer Nature, 2023)
For 2G ethanol production, pentose fermentation and yeast tolerance to lignocellulosic hydrolyzate components are essential to improve biorefinery yields. Generally, physicochemical pre-treatment methodologies are used to facilitate access to cellulose and hemicellulose in plant material, which consequently can generate microbial growth inhibitory compounds, such as furans, weak acids, and phenolic compounds. Because of the unsatisfactory yield of wild-type Saccharomyces cerevisiae during pentose fermentation, the search for xylose-fermenting yeasts tolerant to microbial growth inhibitors has gained attention. In this study, we investigated the ability of the yeasts Pichia guilliermondii G1.2 and Candida oleophila G10.1 to produce ethanol from xylose and tolerate the inhibitors furfural, 5-hydroxymethylfurfural (HMF), acetic acid, formic acid, ferulic acid, and vanillin. We demonstrated that both yeasts were able to grow and consume xylose in the presence of all single inhibitors, with greater growth limitation in media containing furfural, acetic acid, and vanillin. In saline medium containing a mixture of these inhibitors (2.5–3.5 mM furfural and HMF, 1 mM ferulic acid, 1–1.5 mM vanillin, 10–13 mM acetic acid, and 5–7 mM formic acid), both yeasts were able to produce ethanol from xylose, similar to that detected in the control medium (without inhibitors). In future studies, the proteins involved in the transport of pentose and tolerance to these inhibitors need to be investigated.
Keywords: Bioenergy; Bioethanol; Fermentation; Xylose; Yeast